2022
DOI: 10.1021/acs.jmedchem.1c01565
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Inhibition of the Mycobacterium tuberculosis Phosphopantetheinyl Transferase PptT by Amidinoureas

Abstract: A newly validated target for tuberculosis treatment is phosphopantetheinyl transferase, an essential enzyme that plays a critical role in the biosynthesis of cellular lipids and virulence factors in Mycobacterium tuberculosis . The structure–activity relationships of a recently disclosed inhibitor, amidinourea (AU) 8918 ( 1 ), were explored, focusing on the biochemical potency, determination of whole-cell on-target activity for active compounds, and profiling of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…Further results on 79 have just been released, including that while this compound does not inhibit CYP3A4 or hERG (IC 50 s > 30 μM) it does cause cardiotoxicity through inhibition of two other ion channels (Ca 2+ and Na + ) . However, initial SAR studies revealed that appropriate para -substitution of the phenyl ring could substantially diminish these interactions without reducing in vitro potency.…”
Section: Preclinical Promisesmentioning
confidence: 99%
“…Further results on 79 have just been released, including that while this compound does not inhibit CYP3A4 or hERG (IC 50 s > 30 μM) it does cause cardiotoxicity through inhibition of two other ion channels (Ca 2+ and Na + ) . However, initial SAR studies revealed that appropriate para -substitution of the phenyl ring could substantially diminish these interactions without reducing in vitro potency.…”
Section: Preclinical Promisesmentioning
confidence: 99%
“…The H2L stage, in many organizations or consortiums, represents the point at which a full medicinal chemistry team is committed to the project. During this stage, structure activity and property relationships are further established and solutions to factors such as in vitro biological activity (enzymatic or cellular), absorption, distribution, metabolism, excretion, or in vitro toxicity are sought . If satisfactory molecules are identified and a certain degree of biological activity is established, typically in an in vivo disease model, a lead series is declared, and the project can advance to the lead optimization stage .…”
Section: Designmentioning
confidence: 99%
“…Therefore, care should be exercised when interpreting chemical-genetic interactions and such studies should be coupled with mass spectrometry drug-uptake quantification to differentiate between these various possibilities ( Davis et al., 2014 ; Planck and Rhee, 2021 ). Further, structural and/or biochemical approaches can be used to identify the target of a particular compound, helping to differentiate between a direct or an indirect mechanism for a specific chemical-genetic interaction ( Pellecchia et al., 2002 ; Zhang et al., 2020 ; Ottavi et al., 2022 ).…”
Section: The Mycobacterial Envelope As a First Line Of Intrinsic Anti...mentioning
confidence: 99%